PERSONAL BRANDING KOMEDIAN DEWANGGA PRIBADITYA ARIF MELALUI MEDIA SOSIAL INSTAGRAM @dewanggaya_ - Chisma Haryati Kartika; Estu Widiyowati (Solidaritas, 2025)
This study aims to describe and analyze the personal branding strategy implemented by comedian Dewangga Pribaditya Arif through his Instagram account @dewanggaya_ as an effort to build a distinctive self-image amidst the competition among digital creators. Using a qualitative descriptive approach, this study collected data through interviews and documentation, then analyzed the phenomenon based on Peter Montoya's eight Personal Branding concepts. The results show that Dewangga has successfully implemented all eight branding aspects consistently. Dewangga specializes in flexible comedic acting, supported by a friendly and humble personality. He creates a difference through absurd comedy material with plot twists related to everyday life in Malang Regency. This branding success is supported by consistency in uploading content (appearance), maintaining a unified image on social media and in the real world, demonstrating steadfastness in his work, and maintaining a good reputation by filtering content to keep it entertaining without offending others. This study concludes that Instagram is an effective platform for non-celebrity individuals to build a structured and impactful personal image, generating professional career opportunities such as endorsements and MC roles. Keywords: Personal Branding, Instagram, Comedian, Peter Montoya, Absurd Comedy.